-6K+7K=1K or K
-6k + 7k = k
k + 6k - 13 = 177k = 30k = 30/7k = 4.2857
-47 + 6k = 3k - 2Add 47 to each side:6k = 3k +45Subtract 3k from each side:3k = 45Divide each side by 3:k = 15
26-7k=6k First, add 7k to get k on one side. 26-7k+7k=6k+7k 26=13k Divide both sides by 13 to get k by itself. 26/13=13k/13 2=k The answer is 2.
-6k + 7k = k or 7k- 6k = k or Factor out 'k' k(-6 + 7) = k(1) = k
8k = 6k - 26 8k - 6k = 6k - 6k - 26 2k = -26 2k / 2 = -26 / 2 k = -13. The answer is k = -13.
11 + 6k = 65 Subtract 11 from both sides: 6k = 65-11 6k = 54 Divide by 6 to get k: k = 54/6 k = 9
-6K+7K=1K or K
given: 4w+(6k-3w)+(2-k)remove parentheses: 4w+6k-3w+2-kcollect like terms: 4w-3w+6k-k+2simplify: w+5k+2
-6k + 7k = k
Yes the suffix 'K' or 'k' is used to denote thousands. So 6K is six thousand or 6000.
k + 6k - 13 = 177k = 30k = 30/7k = 4.2857
It is simply: 6k
-6k+7k = 1k or normally k on its own.
k is a variable, 6 is a coefficient.
-47 + 6k = 3k - 2Add 47 to each side:6k = 3k +45Subtract 3k from each side:3k = 45Divide each side by 3:k = 15